National policy-making domestication of global trends - Alasuutari, Pertti; Qadir, Ali; Pertti Alasuutari (Routledge advances in sociology, 2014)
Notions of social change are often divided into local versus international. But what actually happens at the national level--where policies are ultimately made and implemented--when policymaking is interdependent worldwide? How do policymakers take into account the prior choices of other countries? Far more research is needed on the process of interdependent decision-making in the world polity.National Policy-Making: Domestication of Global Trends offers a unique set of hybrid cases which straddle these disciplinary and conceptual divides. The volume brings together well-researched case studies of policy-making from across the world, which speak to practical issues but also challenge current theories of global influence in local policies. Distancing itself from approaches which conceive narrowly of policy transfer as a 'one-way street' from powerful nations to weaker ones, this book argues instead for an understanding of national decision-making processes that emphasise cross-national comparisons and domestic field battles around the introduction of worldwide models. The case studies in this collection show how national policies appear to be synchronised globally, yet are developed with distinct 'national' flavours. Presenting new theoretical ideas and empirical cases, this book is aimed globally at scholars of political science, international relations, comparative public policy, and sociology